THE COMMUNITY OWN RESOURCE PERSONS MODEL: A CASE STUDY OF YUMBE DISTRICT IN UGANDA, IMPLEMENTED BY MCJL UNDER THE JOINT INITIATIVE FOR STRATEGIC RELIGIOUS ACTION PROGRAMME (Lex localis - Journal of Local Self-Government, 2025)
The Community Own Resource Persons (CORPs) Model, developed in Yumbe District, Uganda, addresses escalating tensions between predominantly Muslim and Christian populations by enhancing interfaith tolerance and social cohesion. This case study reveals how community-selected individuals, integrated into local faith structures, facilitate conflict resolution, advocacy, and education through a participatory learning approach. The model emphasizes inclusivity by ensuring representation of women and youth, fostering a collective resilience against harmful traditional practices and facilitating awareness of Freedom of Religion and Belief (FoRB). Data collected indicated significant improvements in community well-being, with CORPs mediating land disputes, advocating for property rights, and promoting communal harmony. Despite logistical challenges, the model has successfully mobilized faith leaders, created referral networks, and utilized social media for outreach. The findings underscore the crucial role of faith actors in peace building, advocating for enhanced support for inclusive dialogues that protect marginalized voices. In conclusion, the CORPs model presents a scalable framework that not only mitigates existing tensions but also contributes to broader national identity and unity by addressing the diverse cultural and religious dynamics within Yumbe District. Recommendations include expanding training programs for faith leaders and integrating CORPs into broader community development initiatives to further support social resilience.